(untitled) (European Journal of Education and Psychology, 2018)
Morphological awareness can play an important role in the process of literacy refers. It presents an experimental validation study with a sample of students pre-readers in kindergarten and first students of Primary Education on Instrumento de Evaluación de la Conciencia Morfológica Oral (IECMO) designed for study Spanish and focuses on the evaluation of the three dimensions of morphological awareness: a) the morphology inflexional, b) derivacional morphology, and c) compound words. This study involved a total of fifty students belonging to the last year of kindergarten and first grade education. Their ages ranged from 5 to 7 years. In conjunction with experimental validation study presented the initial results of reliability testing for internal consistency, item analysis and stable test-retest analysis and the validity of the proof, or apparent conflict of content and construct or theoretical. The results obtained in the analysis of the psychometric properties of the instrument to verify verify both the validity of content and construct, as the reliability of IECMO. This tool can be very useful, since teachers should take into account the role of morphological awareness in learning and mastering different metalinguistic skills.